Cross-sectional study of the anthropometric profile and nutrient status of elite female ice hockey players: differences by play position - Jiménez-Casquet, M. J.; Conde-Pipo, J.; Valenzuela-Barranco, I.; Rienda-Contreras, R.; Olea-Serrano, F.; Monserrat-Mesquida, M.; Tur, J. A.; Bouzas, C.; Mariscal-Arcas, M. (Nutrients, 2024)
Both the characteristics of ice hockey and the environmental conditions in which it is played affect the maintenance of the player`s nutritional status and, therefore, their state of health and performance. The primary aim of this work was to examine the anthropometric profile, estimated energy expenditure, and macronutrient and micronutrient dietary intake of elite female ice hockey players by play position. As a secondary aim, their dietary intakes were compared with the recommendations. Hypotheses suggest variations in body composition based on ice hockey players` positions, with the expectation that these athletes may not align with energy and nutrient recommendations. Fifteen elite female ice hockey players were anthropometrically measured, basal metabolic rate and total energy expenditure were estimated, a 3-day, 24 h recall questionnaire was registered, and the results were compared with the recommended dietary intake for the Spanish population. Each player`s position on the field requires an individualized physical and nutritional approach. There are no significant imbalances (p > 0.05) between energy and nutrient intake in relation to the Recommended Daily Intake (RDI); however, increasing the consumption of vegetables and seafood while reducing meat and fat intake would assist these athletes in maintaining a healthier energy balance, optimizing body composition, and aligning with nutritional parameters that are better suited to enhance physical performance.